Slippery space and sticky places: evidence from the Indian IT industry. Issue 1 (1st January 2020) - Ray, Pradeep Kanta; Kathuria, Vinish; Kumar, Vikas
ABSTRACT: Sweeping changes wrought by globalization and disaggregation of global value chains by multinational companies poses challenges to territorial theories of competitiveness. Contemplating notions propounded by economic geographers and strategic management scholars, the paper examines firm-level competitiveness at the intersection of spatially mobile versus spatially bound geographies. It aims to understand if linkages between actors within sticky local ecosystems are sufficient for firm internationalization from emerging economies. The paper empirically uncovers how cognitive ties at both local and global levels contribute to the internationalization of firms from emerging economies such as India that have a lower level of development and which suffer from institutional voids.